2013
DOI: 10.1080/09658211.2013.788660
|View full text |Cite
|
Sign up to set email alerts
|

Dying to remember, remembering to survive: Mortality salience and survival processing

Abstract: Processing items for their relevance to survival improves recall for those items relative to numerous other deep processing encoding techniques. Perhaps related, placing individuals in a mortality salient state has also been shown to enhance retention of items encoded after the morality salience manipulation (e.g., in a pleasantness rating task), a phenomenon we dubbed the "dying-to-remember" (DTR) effect. The experiments reported here further explored the effect and tested the possibility that the DTR effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 46 publications
3
19
0
1
Order By: Relevance
“…We suggested that such benefits might extend to information processing. Consistent with the idea that MS enhances motivation to process information, we provided some evidence that MS increases cognitive depth and complexity ; see also Burns, Hart, Kramer, & Burns, 2013). Independent raters who coded the written responses to the mortality and control questions found the responses to the mortality questions to be more complex, deep, meaningful, and sophisticated.…”
supporting
confidence: 72%
See 3 more Smart Citations
“…We suggested that such benefits might extend to information processing. Consistent with the idea that MS enhances motivation to process information, we provided some evidence that MS increases cognitive depth and complexity ; see also Burns, Hart, Kramer, & Burns, 2013). Independent raters who coded the written responses to the mortality and control questions found the responses to the mortality questions to be more complex, deep, meaningful, and sophisticated.…”
supporting
confidence: 72%
“…Although our subsequent findings (Burns et al, 2013) were consistent with a functional connection, our studies did not go so far as to match the mortality and survival manipulations on key factors, making them difficult to compare directly. Klein sought to resolve this by comparing the effects of a dying scenario to those of the survival scenario as well as a pleasantness rating control task.…”
mentioning
confidence: 49%
See 2 more Smart Citations
“…Burns, Hart, Kramer, and Burns (2014) considered the "dying-to-remember" (DTR) effect, where participants are placed in a mortality salient state, and tested if the DTR effect was related to survival processing. Burns et al found an association with the DTR effect and an increase in item-specific processing.…”
Section: A Meta-analysis Of the Survival Processing Advantage In Memorymentioning
confidence: 99%